Effect of Lasalocid or Monensin on feedlot (grain) bloat in cattle - E.E. Bartley; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1983)
Lasalocid or monensin (600 mg per 1000 lb body weight daily) was tested on cattle bloating on high grain diets. Bloat was reduced 92% by Lasalocid and 64% by monensin. When fed throughout the finishing period, lasalocid at 300 mg per 1000 lb body weight effectively prevented bloat from developing. However, 600 mg was required to control bloat in cattle that were already bloating.
Keywords: Cattlemen& #x27; s Day; 1983; Report of progress (Kansas State University. Agricultural Experiment Station); 427; Beef; Lasalocid; Monensin; Bloat